A gradient carbon-coated modified sodium iron phosphate pyrophosphate positive electrode material, a preparation method and applications thereof
Patent Information
- Application Number
- CN202611295641.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-30
AI Technical Summary
作为该材料体系中的重要一员,磷酸焦磷酸铁钠(NFPP)因资源丰富、成本低廉及环境友好等特性而备受关注,然而其本征电子导电率较低,电极反应动力学迟缓,严重制约了活性物质在较高倍率下的比容量发挥
[0019]本发明具有的有益效果是:本发明提供的梯度碳包覆改性磷酸焦磷酸铁钠正极材料通过构建多级梯度碳包覆结构实现导电性能的显著提升。在一级颗粒层面,磷酸焦磷酸铁钠活性物质基体表面包覆有由有机碳源热解物形成的第一碳质层,该层连续致密且与基体结合紧密,为后续导电网络的构建提供了基础界面;在二级颗粒层面,多个一级颗粒团聚形成团聚体后,其外表面进一步包覆第二碳质层,该层在包覆过程中渗入一级颗粒间的缝隙,与第一碳质层衔接形成连续导电通路,同时对一级颗粒外露部位实施二次包覆,增加导电物质覆盖量,从而构筑长程有序的导电网络。在碳质组分搭配上,第二碳质层同时包含有机碳源热解物以及一维无机碳纳米材料和二维无机碳纳米材料,其中有机碳源热解物保障导电网络的连续致密性,一维与二维无机碳纳米材料在颗粒表面及缝隙中交错搭接,形成多维空间导电骨架,两者协同分布,既强化了各导电单元间的界面结合,又丰富了电荷传输路径,最终有效改善材料的电子导电性能并提升高倍率下的比容量发挥。
Smart Images

Figure CN123017937A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a gradient carbon-coated modified sodium iron pyrophosphate cathode material, its preparation method, and its application. Background Technology
[0002] Polyanionic sodium-ion battery cathode materials exhibit significant advantages in structural stability and cycle life due to their robust three-dimensional framework structure and strong covalent bonding. These materials exhibit small lattice strain and slow structural degradation during charge and discharge, thus possessing excellent long-term cycle stability. They demonstrate irreplaceable competitiveness, particularly in large-scale energy storage applications where safety and durability requirements are extremely stringent. Sodium iron pyrophosphate (NFPP), an important member of this material system, has attracted considerable attention due to its abundant resources, low cost, and environmental friendliness. However, its low intrinsic electronic conductivity and sluggish electrode reaction kinetics severely limit the specific capacity of the active material at higher rates.
[0003] To address this deficiency, existing technologies generally employ carbon coating modification strategies, which improve the electrical contact between particles by constructing conductive carbon layers on the surface of active particles. However, such conventional methods can usually only form simple core-shell structures with single coating. The charge transfer between particles still relies on limited point contact or local adjacency. There is a lack of continuous, long-range conductive connections between the coated carbon layers, making it difficult to construct an efficient and interconnected overall conductive framework. As a result, the improvement effect on the overall conductivity of the material is extremely limited. Summary of the Invention
[0004] The purpose of this invention is to provide a gradient carbon-coated modified sodium iron pyrophosphate cathode material, its preparation method, and its application, so as to solve the problems existing in the background art.
[0005] The technical solution of the present invention includes: a gradient carbon-coated modified sodium iron pyrophosphate cathode material, wherein the cathode material comprises secondary particles formed by the agglomeration of primary particles, the primary particles comprising an active material matrix and a first carbonaceous layer coating the outside thereof, and the secondary particles comprising agglomerates of primary particles and a second carbonaceous layer coating the outside thereof; the first carbonaceous layer and the second carbonaceous layer contain a first carbonaceous component, and the second carbonaceous layer further contains a second carbonaceous component, wherein the first carbonaceous component is an organic carbon source pyrolysis product, and the second carbonaceous component comprises at least one of one-dimensional inorganic carbon nanomaterials and two-dimensional inorganic carbon nanomaterials.
[0006] Preferably, the total mass of the first carbonaceous component and the second carbonaceous component accounts for 1.5% to 2.5% of the total mass of the cathode material, the mass ratio of the first carbonaceous component to the second carbonaceous component is (2 to 4):1, and the mass ratio of the one-dimensional inorganic carbon nanomaterial to the two-dimensional inorganic carbon nanomaterial is (3 to 5):1.
[0007] Preferably, the organic carbon source pyrolyte includes any one or more of sucrose pyrolyte, glucose pyrolyte, citric acid pyrolyte, starch pyrolyte, and polyethylene glycol pyrolyte; the one-dimensional inorganic carbon nanomaterial includes carbon nanotubes; and the two-dimensional inorganic carbon nanomaterial includes reduced graphene oxide.
[0008] Preferably, the chemical formula of the active substance matrix is Na. 4-x Fe 3-y (PO4) 2-z P2O7, where: 0<x≤0.6, 0<y≤0.6, 0<z≤0.6, (4-x):(3-y)=(1.32~1.42):1.
[0009] The technical solution of the present invention also includes: a method for preparing the above-mentioned gradient carbon-coated modified iron pyrophosphate sodium cathode material, which includes the following steps:
[0010] Iron source, sodium source, phosphorus source, organic carbon source and water are mixed and sand-milled, and the resulting sand-milled slurry is spray-dried to obtain the first precursor;
[0011] The first precursor is subjected to a first heat treatment, and the resulting first sintered material is pulverized.
[0012] The second carbonaceous component is mixed with the pulverized first sintered material in a solid phase to obtain the second precursor.
[0013] The second precursor is subjected to a second heat treatment to obtain the cathode material.
[0014] Preferably, the organic carbon source accounts for 6% to 9% of the total mass of the iron source, the sodium source, and the phosphorus source; the solid content of the sand milling slurry is 20% to 40%, and the volume-based median particle size of the solid matter in the sand milling slurry is 0.1 μm to 0.3 μm; the spray drying conditions are: inlet air temperature 180 to 260°C, and outlet air temperature 90 to 130°C.
[0015] Preferably, the first heat treatment is carried out in an inert atmosphere, the temperature of the first heat treatment is 200~400℃, the time is 2h~6h, and the heating rate is 1℃ / min~5℃ / min; the pulverization treatment is air jet milling, and the volume-based median particle size of the pulverized first sinter is 2μm~5μm.
[0016] Preferably, the second carbonaceous component accounts for 0.3% to 1% of the total mass of the second precursor; the second heat treatment is carried out in an inert atmosphere, the temperature of the second heat treatment is 500 to 600°C, the time is 6 to 12 hours, and the heating rate is 1°C / min to 5°C / min.
[0017] Preferably, the iron source includes any one or more of elemental iron, ferrous oxalate, ferric phosphate, ferric phosphate dihydrate, ferric oxide, ferrous oxalate, ferric nitrate, ferric pyrophosphate, and ferrous pyrophosphate; the sodium source includes any one or more of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, sodium pyrophosphate, sodium oxalate, and sodium acetate; and the phosphorus source includes any one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, ferric pyrophosphate, sodium pyrophosphate, and sodium dihydrogen phosphate.
[0018] The technical solution of the present invention also includes the application of the above-mentioned gradient carbon-coated modified iron sodium pyrophosphate cathode material in electrochemical energy storage devices.
[0019] The beneficial effects of this invention are as follows: The gradient carbon-coated modified sodium iron pyrophosphate cathode material provided by this invention achieves a significant improvement in conductivity by constructing a multi-level gradient carbon coating structure. At the primary particle level, the surface of the sodium iron pyrophosphate active material matrix is coated with a first carbonaceous layer formed by the pyrolysis of organic carbon sources. This layer is continuous, dense, and tightly bonded to the matrix, providing a basic interface for the subsequent construction of the conductive network. At the secondary particle level, after multiple primary particles agglomerate to form aggregates, their outer surfaces are further coated with a second carbonaceous layer. During the coating process, this layer penetrates into the gaps between the primary particles, connecting with the first carbonaceous layer to form a continuous conductive path. At the same time, the exposed parts of the primary particles are coated a second time, increasing the coverage of conductive material, thereby constructing a long-range ordered conductive network. In terms of carbonaceous composition, the second carbonaceous layer simultaneously contains organic carbon source pyrolysis products, as well as one-dimensional and two-dimensional inorganic carbon nanomaterials. The organic carbon source pyrolysis products ensure the continuity and density of the conductive network, while the one-dimensional and two-dimensional inorganic carbon nanomaterials are interleaved on the particle surface and in the gaps to form a multi-dimensional spatial conductive framework. The synergistic distribution of the two not only strengthens the interfacial bonding between each conductive unit but also enriches the charge transport path, ultimately effectively improving the electronic conductivity of the material and enhancing the specific capacity at high rates. Attached Figure Description
[0020] Figure 1 This is the XRD pattern of the cathode material prepared in Example 1 of this invention.
[0021] Figure 2 The above are electrochemical curves of the cathode materials prepared in Examples 1-2 and Comparative Examples 1-3 of this invention. Detailed Implementation
[0022] To better illustrate the objectives, complete technical approach, and advantages of this invention, the following detailed description will be provided in conjunction with specific embodiments. However, the embodiments described below are only a part of the embodiments of this invention and do not include all embodiments. Other embodiments that can be obtained by those skilled in the art without creative effort based on the embodiments of this invention are all within the protection scope of this invention.
[0023] In the embodiments described below, unless otherwise specified, the conventional methods used are all technical means recognized or commonly used by those skilled in the art, and the instruments, reagents, consumables, etc. used in the embodiments of the present invention can be obtained through legitimate commercial channels.
[0024] This invention provides a gradient carbon-coated modified sodium iron pyrophosphate cathode material. The cathode material comprises secondary particles formed by the agglomeration of multiple primary particles. Each primary particle includes an active material matrix and a first carbonaceous layer coating its exterior. Each secondary particle comprises an agglomeration of primary particles and a second carbonaceous layer coating its exterior. Both the first and second carbonaceous layers contain a first carbonaceous component, and the second carbonaceous layer also contains a second carbonaceous component. The first carbonaceous component is an organic carbon source pyrolysis product, and the second carbonaceous component includes at least one of one-dimensional inorganic carbon nanomaterials and two-dimensional inorganic carbon nanomaterials.
[0025] In the gradient carbon-coated modified sodium iron pyrophosphate cathode material provided by the above scheme, the primary particles themselves are already coated with a first carbonaceous layer as a conductive layer. Based on this, multiple primary particles agglomerate to form the core structure of secondary particles. During this agglomeration process, the primary particles can form sufficient and close contact, which is beneficial for charge transfer between particles. Simultaneously, when the second carbonaceous layer coats the outer surface of the primary particle agglomeration composed of multiple primary particles, the second carbonaceous layer can penetrate and fill the gaps between the primary particles. During the filling process, it forms a continuous conductive connection with the original first carbonaceous layer on the surface of the primary particles, thereby constructing a long-range ordered conductive path. Furthermore, the second carbonaceous layer can also coat the exposed parts of the primary particles that are not blocked by adjacent particles, which is equivalent to a secondary coating of the primary particles on the basis of the first carbonaceous layer. This ensures the continuity and integrity of the conductive network and further increases the coverage of conductive material on the particle surface, thereby effectively improving the overall electronic conductivity of the material.
[0026] Regarding the selection and combination of carbonaceous components, the first carbonaceous layer uses organic carbon source pyrolysis as the coating material. Utilizing the in-situ pyrolysis reaction of the organic carbon source during heat treatment, a continuous and dense coating layer can be formed on the surface of the conductive substrate, which is beneficial for achieving uniform and stable interfacial contact. The second carbonaceous layer simultaneously includes the organic carbon source pyrolysis from the first carbonaceous component and at least one of one-dimensional and two-dimensional inorganic carbon nanomaterials from the second carbonaceous component. The organic carbon source pyrolysis in the second carbonaceous layer further enhances the continuity and density of the conductive network, while the one-dimensional and two-dimensional inorganic carbon nanomaterials are interleaved and overlapped on the outer surface of the primary particle agglomerates and in the gaps between particles, forming a conductive framework with a multi-dimensional spatial configuration. The organic carbon source pyrolysis is uniformly dispersed in this three-dimensional conductive framework, effectively filling the framework voids and strengthening the interfacial bonding between each conductive unit. The synergistic effect of both significantly improves the electronic conductivity of the sodium iron pyrophosphate cathode material, thereby enhancing the specific capacity of the material under high-rate conditions.
[0027] The active material matrix is sodium iron pyrophosphate, with the chemical formula Na. 4-x Fe 3-y (PO4) 2- z P2O7, where: 0 < x ≤ 0.6, 0 < y ≤ 0.6, 0 < z ≤ 0.6, (4-x):(3-y) = (1.32~1.42):1. More preferably, 0.2 ≤ x ≤ 0.6, 0.2 ≤ y ≤ 0.5, 0.2 ≤ z ≤ 0.6.
[0028] To optimize the overall electrochemical performance of the material, the mass ratio of each component in the aforementioned cathode material needs to be reasonably controlled. Specifically, the mass of the active material matrix should be controlled at 95% or more of the total mass of the cathode material, preferably 98% or more, to ensure that the sodium iron pyrophosphate active material dominates the electrode, thereby fully preserving and utilizing the theoretical specific capacity of the cathode material.
[0029] Meanwhile, the total mass of the first carbonaceous component and the second carbonaceous component accounts for 1.5% to 2.5% of the total mass of the cathode material, and the preferred mass ratio of the first carbonaceous component to the second carbonaceous component is (2~4):1. This is because if the total carbonaceous component content is too low, it is difficult to form a continuous and effective conductive path on the particle surface and between particles, resulting in limited improvement on the intrinsic conductivity of the material. Conversely, if the carbonaceous component content is too high, the proportion of non-electrochemically active inert components in the cathode material will be too high, directly reducing the material's mass energy density. Therefore, limiting the total amount of carbonaceous component to the above range can effectively improve the conductivity of the cathode material while ensuring a high energy density.
[0030] The reason for limiting the ratio of the first carbonaceous component to the second carbonaceous component within the aforementioned range is that: when constructing a multidimensional conductive framework, the one-dimensional or two-dimensional inorganic carbon nanomaterials in the second carbonaceous component will form certain pores within the secondary particles and between particle stacks, leading to a decrease in the material's tap density and compaction density, thus affecting the electrode's volumetric energy density. If the relative proportion of the second carbonaceous component is too high, the excessive amount of one-dimensional or two-dimensional inorganic carbon nanomaterials will significantly increase porosity and excessively reduce compaction density; if the relative proportion of the second carbonaceous component is too low, it will be difficult to fully utilize the advantages of inorganic carbon nanomaterials in constructing a multidimensional conductive framework, and the improvement in conductivity will be limited. In other words, controlling the mass ratio of the first carbonaceous component to the second carbonaceous component within the aforementioned preferred range can fully utilize the conductivity gain effect of the second carbonaceous component while reasonably suppressing the excessive increase in porosity caused by the excessive introduction of inorganic carbon nanomaterials, thereby achieving an effective balance between improving conductivity and maintaining compaction density, and avoiding sacrificing the electrode's volumetric energy density in pursuit of conductivity at the expense of other aspects.
[0031] In the preferred technical solution, the second carbonaceous component simultaneously contains one-dimensional and two-dimensional inorganic carbon nanomaterials. The one-dimensional inorganic carbon nanomaterials have a high aspect ratio, enabling them to form inter-particle overlaps and act as directional conductors. The two-dimensional inorganic carbon nanomaterials have a large specific surface area and lamellar extensibility, allowing them to form a conductive substrate with planar coverage and overlapping lamellar layers on the particle surface and between particles. The two materials work together synergistically, with the one-dimensional material interspersed among the lamellar networks constructed by the two-dimensional material, forming a multi-dimensional spatial conductive framework with point-line-plane interlinking. Compared to the addition of a single-dimensional inorganic carbon nanomaterial, this provides a richer and more three-dimensional conductive pathway, thereby more effectively reducing electrode polarization, promoting rapid charge transfer between the active material matrix and the conductive network, and further improving the rate performance and active material utilization rate during charge and discharge processes.
[0032] Preferably, the mass ratio of one-dimensional inorganic carbon nanomaterials to two-dimensional inorganic carbon nanomaterials is (3~5):1. Within this ratio range, one-dimensional inorganic carbon nanomaterials can construct long-range conductive pathways, while two-dimensional inorganic carbon nanomaterials act as layered bridges to connect the gaps between one-dimensional inorganic carbon nanomaterials, forming a three-dimensional synergistic conductive network. At the same time, this ratio can avoid the phenomenon of one-dimensional inorganic carbon nanomaterials entanglement and two-dimensional inorganic carbon nanomaterials stacking and agglomerating, significantly improving the electronic conductivity of the material while ensuring the high-compact characteristics of the cathode material.
[0033] To obtain the above-mentioned gradient carbon-coated modified sodium iron pyrophosphate cathode material, the present invention provides the following specific preparation method:
[0034] S1. Iron source, sodium source, phosphorus source, organic carbon source and water are mixed and sand-milled, and the resulting sand-milled slurry is spray-dried to obtain the first precursor.
[0035] The iron source can be any one or more of elemental iron, ferrous oxalate, ferric phosphate, ferric phosphate dihydrate, ferric oxide, ferrous oxalate, ferric nitrate, ferric pyrophosphate, and ferrous pyrophosphate; the sodium source can be any one or more of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, sodium pyrophosphate, sodium oxalate, and sodium acetate; the phosphorus source can be any one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, ferric pyrophosphate, sodium pyrophosphate, and sodium dihydrogen phosphate; and the organic carbon source can be any one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol, such that the first carbonaceous component formed is any one or more of sucrose pyrolysis product, glucose pyrolysis product, citric acid pyrolysis product, starch pyrolysis product, and polyethylene glycol pyrolysis product.
[0036] In this step, the iron, sodium, phosphorus, and organic carbon sources are thoroughly mixed with water through sand milling. The raw material components are refined to a suitable particle size under mechanical grinding, achieving a homogeneous dispersion. Subsequently, spray drying yields a first precursor with uniform particle size distribution and good flowability. The morphology and particle size of this first precursor are controllable, which is beneficial for sufficient contact and uniform reaction between components during subsequent solid-phase reactions. In the subsequent heat treatment, the organic carbon source undergoes in-situ pyrolysis at high temperature. The released reducing substances reduce the ferric iron in the iron source to ferrous iron, thereby promoting the crystal phase formation of the sodium iron pyrophosphate active material matrix. Simultaneously, the grain boundary carbon generated by the pyrolysis of the organic carbon source is deposited in-situ on the surface of the newly formed active material matrix, forming a continuous and dense first carbonaceous layer. This in-situ generation method ensures a tight interfacial bond between the first carbonaceous layer and the active material matrix, avoiding the common problem of poor interfacial contact when introducing external carbon layers, which is beneficial for constructing efficient and continuous electron transport pathways.
[0037] Based on the phase composition and stoichiometric ratio requirements of the target product, the amount of organic carbon source added in this step accounts for 6% to 9% of the total mass of iron, sodium, and phosphorus sources. This addition range aims to ensure a sufficient supply of carbon sources during the heat treatment process to meet the needs of constructing the first and second carbonaceous layers, while providing a sufficient reducing atmosphere to promote the full reduction of ferric iron to ferrous iron, thus ensuring the pure-phase synthesis of the target product sodium ferric pyrophosphate active matrix.
[0038] In this step, it is preferable to control the solid content of the sand milling slurry at 20% to 40% to ensure that the sand milling slurry has suitable fluidity, sand milling efficiency and spray drying efficiency.
[0039] In the slurry system, the iron source (such as ferric phosphate dihydrate) is insoluble in water and exists in the form of solid particles. After sand milling, it becomes nanoscale primary particles. The sodium source, phosphorus source, and organic carbon source are soluble in water and are uniformly dispersed in the liquid phase. During spray drying, water evaporates rapidly, and the dissolved components precipitate out and uniformly coat the surface of the iron source particles, thereby forming a first precursor with uniform stoichiometry and close component contact at the single particle scale. Based on this, another key point of this step is to control the sand milling conditions so that the volumetric median particle size of the solid matter in the sand-milled slurry is 0.1μm~0.3μm, and the D90 of the particle size distribution is not greater than 0.9μm, thereby obtaining uniformly dispersed nanoscale primary particles. During the spray granulation process, each component can achieve uniform distribution by relying on the nanoscale primary particles as the smallest unit of the core. This provides a structural basis for subsequent heat treatment: it can not only significantly shorten the diffusion path of the solid-phase reaction and ensure that the reaction is fully carried out, but also facilitate the uniform control of the particle size of the primary particles in the calcined material. At the same time, it ensures that the grain boundary carbon generated by the in-situ pyrolysis of the organic carbon source is uniformly deposited on the particle surface to form a complete and dense carbon coating layer.
[0040] In this step, the preferred conditions for spray drying are: inlet air temperature of 180~260℃ and outlet air temperature of 90~130℃. Within this temperature range, the moisture in the sand mill slurry droplets can evaporate at a suitable rate, which ensures that the droplets can be quickly solidified and formed in the drying chamber, avoiding incomplete drying, particle sticking to the wall, or poor sphericity due to excessively low temperature. It also prevents premature decomposition of organic carbon source or local overheating caused by excessively high temperature, resulting in particle cracking and morphological defects, thereby obtaining first precursor particles with uniform particle size distribution and good sphericity.
[0041] S2. Perform a first heat treatment on the first precursor and then crush the resulting first sintered material.
[0042] In this step, the first heat treatment is carried out in an inert atmosphere, which can be a nitrogen atmosphere or an argon atmosphere. The preferred conditions for the first heat treatment are: temperature 200~400℃, time 2h~6h, and heating rate 1℃ / min~5℃ / min. Under these preferred conditions, the organic carbon source undergoes preliminary pyrolysis, generating reducing substances to promote the pre-reduction of ferric iron in the iron source. Simultaneously, the carbonaceous products generated from the pyrolysis of the organic carbon source are deposited in situ on the surface of the raw material particles, forming a precursor bulk coating layer for the first carbonaceous component, providing a material basis for the subsequent graphitization and densification of the carbonaceous component.
[0043] After the first heat treatment, the resulting first sintered material is pulverized to eliminate slight sintering adhesion between particles, obtaining powder with a uniform particle size distribution. This provides a good physical basis for the uniform distribution of carbonaceous components and the full development of the crystal structure during the subsequent second heat treatment. The pulverization method can be air jet milling. The volumetric median particle size of the pulverized first sintered material should be controlled within 2μm to 5μm, and the D90 of the particle size distribution should not exceed 10μm.
[0044] S3. The second carbonaceous component is mixed with the pulverized first sintered material in a solid phase to obtain the second precursor.
[0045] The preferred amount of the second carbonaceous component is 0.3% to 1% of the total mass of the second precursor. The second carbonaceous component includes one-dimensional inorganic carbon nanomaterials and two-dimensional inorganic carbon nanomaterials. The one-dimensional inorganic carbon nanomaterials include carbon nanotubes, and the two-dimensional inorganic carbon nanomaterials include reduced graphene oxide.
[0046] S4. Perform a second heat treatment on the second precursor to obtain a cathode material with a volume-based median particle size in the range of 5μm~10μm.
[0047] In this step, the second heat treatment is carried out in an inert atmosphere, which can be a nitrogen atmosphere or an argon atmosphere. The preferred conditions for the second heat treatment are: temperature 500~600℃, time 6h~12h, and heating rate 1℃ / min~5℃ / min. Under these heat treatment conditions, the crystal phase structure of the sodium iron pyrophosphate active material matrix is further developed and perfected, the crystal order is improved, and the purity and crystallinity of the target crystal phase are fully guaranteed. Meanwhile, the first carbonaceous component, which was initially pyrolyzed but not yet fully densified during the first heat treatment, undergoes further carbonization and rearrangement during the second heat treatment, becoming more densified. In this process, it interpenetrates, overlaps, and tightly binds with the one-dimensional and two-dimensional inorganic carbon nanomaterials in the second carbonaceous component. The first carbonaceous component is distributed in the gaps and interface regions of the multidimensional conductive framework constructed by carbon nanotubes and reduced graphene oxide, and finally solidifies to form a continuous, dense, and structurally stable gradient carbon coating layer. This achieves a strong bond between the first and second carbonaceous layers and the construction of an integrated conductive network, and alleviates the problems of powder shedding and electrode brittleness under high pressure density during electrode preparation.
[0048] Based on the above scheme, the gradient carbon-coated modified sodium iron pyrophosphate cathode material provided by this invention achieves excellent comprehensive performance in terms of conductivity and compaction density, with an electronic conductivity reaching 2.0 × 10⁻⁶. -4 With a strength of S / cm or higher, the compacted density can reach 2.0~2.2 g / cm³. 3In terms of electrochemical performance, the specific capacity of the material is effectively improved, with a first-week charging specific capacity ≥112mAh / g and a first-week discharging specific capacity ≥100mAh / g. This indicates that the gradient carbon coating structure is conducive to promoting efficient charge transport in the active material while maintaining the material's volumetric energy density.
[0049] Another aspect of the present invention provides the application of the above-described gradient carbon-coated modified sodium iron pyrophosphate cathode material in electrochemical energy storage devices. Specifically, this cathode material can be used to prepare cathode sheets for sodium-ion batteries, sodium-ion batteries containing the cathode sheets, and electrical devices incorporating the above-described sodium-ion batteries.
[0050] The following are specific embodiments and comparative examples of the present invention. Unless otherwise specified, the amount of each substance added is expressed in parts by mass.
[0051] Example 1
[0052] S1. Take FePO4·2H2O, NaH2PO4, and Na2CO3 in a molar ratio of 2.6:1:1.3, and add 5.6% glucose and 2% citric acid by mass of the above substances. Mix with water and sand mill to prepare a sand mill slurry with a solid content of 30%. The median particle size of the solid substances in the sand mill slurry is 0.1μm~0.2μm by volume reference.
[0053] The obtained sand-milled slurry was spray-dried to obtain the first precursor.
[0054] S2. The first precursor is transferred to a nitrogen atmosphere furnace for a first heat treatment. The temperature of the first heat treatment is 300℃, the time is 2h, and the heating rate is 2℃ / min. The resulting first sintered material is then crushed.
[0055] S3. The second carbonaceous component is mixed with the pulverized first sintered material in a solid-state process to obtain the second precursor. The second carbonaceous component includes carbon nanotubes and reduced graphene oxide, with carbon nanotubes accounting for 0.3% of the mass of the second precursor and reduced graphene oxide accounting for 0.1% of the mass of the second precursor.
[0056] S4. The second precursor is transferred to a nitrogen atmosphere furnace for a second heat treatment. The temperature of the second heat treatment is 550℃, the time is 10h, and the heating rate is 2℃ / min, finally obtaining the cathode material.
[0057] Example 2
[0058] S1. Take FePO4·2H2O, NaH2PO4, and Na2CO3 in a molar ratio of 2.6:1:1.3, and add 5.6% glucose and 2% citric acid by mass of the above substances. Mix with water and sand mill to prepare a sand mill slurry with a solid content of 30%. The median particle size of the solid substances in the sand mill slurry is 0.2μm~0.3μm by volume reference.
[0059] The obtained sand-milled slurry was spray-dried to obtain the first precursor.
[0060] S2. The first precursor is transferred to a nitrogen atmosphere furnace for a first heat treatment. The temperature of the first heat treatment is 300℃, the time is 2h, and the heating rate is 2℃ / min. The resulting first sintered material is then crushed.
[0061] S3. The second carbonaceous component is mixed with the pulverized first sintered material in a solid-state process to obtain the second precursor. The second carbonaceous component includes carbon nanotubes and reduced graphene oxide, with carbon nanotubes accounting for 0.3% of the mass of the second precursor and reduced graphene oxide accounting for 0.1% of the mass of the second precursor.
[0062] S4. The second precursor is transferred to a nitrogen atmosphere furnace for a second heat treatment. The temperature of the second heat treatment is 550℃, the time is 10h, and the heating rate is 2℃ / min, finally obtaining the cathode material.
[0063] Example 3
[0064] S1. Take FePO4·2H2O, NaH2PO4, and Na2CO3 in a molar ratio of 2.6:1:1.3, and add 4.8% glucose and 2% citric acid by mass of the above substances. Mix with water and sand mill to prepare a sand mill slurry with a solid content of 30%. The median particle size of the solid substances in the sand mill slurry is 0.1μm~0.2μm by volume reference.
[0065] The obtained sand-milled slurry was spray-dried to obtain the first precursor.
[0066] S2. The first precursor is transferred to a nitrogen atmosphere furnace for a first heat treatment. The temperature of the first heat treatment is 300℃, the time is 2h, and the heating rate is 2℃ / min. The resulting first sintered material is then crushed.
[0067] S3. The second carbonaceous component is mixed with the pulverized first sintered material in a solid-state process to obtain the second precursor. The second carbonaceous component includes carbon nanotubes and reduced graphene oxide, with carbon nanotubes accounting for 0.5% of the mass of the second precursor and reduced graphene oxide accounting for 0.1% of the mass of the second precursor.
[0068] S4. The second precursor is transferred to a nitrogen atmosphere furnace for a second heat treatment. The temperature of the second heat treatment is 550℃, the time is 10h, and the heating rate is 2℃ / min, finally obtaining the cathode material.
[0069] Comparative Example 1
[0070] S1. Take FePO4·2H2O, NaH2PO4, and Na2CO3 in a molar ratio of 2.6:1:1.3, and add 6% glucose and 2% citric acid by mass of the above substances. Mix with water and sand mill to prepare a sand mill slurry with a solid content of 30%. The median particle size of the solid substances in the sand mill slurry is 0.1μm~0.2μm by volume reference.
[0071] The obtained sand-milled slurry was spray-dried to obtain the first precursor.
[0072] S2. The first precursor is transferred to a nitrogen atmosphere furnace for a first heat treatment. The temperature of the first heat treatment is 300℃, the time is 2h, and the heating rate is 2℃ / min. The resulting first sintered material is then crushed.
[0073] S3. Carbon nanotubes are mixed with the pulverized first sintered material in a solid phase to obtain a second precursor. The carbon nanotubes account for 0.3% of the mass of the second precursor.
[0074] S4. The second precursor is transferred to a nitrogen atmosphere furnace for a second heat treatment. The temperature of the second heat treatment is 550℃, the time is 10h, and the heating rate is 2℃ / min, finally obtaining the cathode material.
[0075] Comparative Example 2
[0076] S1. Take FePO4·2H2O, NaH2PO4, and Na2CO3 in a molar ratio of 2.6:1:1.3, and add 5.6% glucose and 2% citric acid by mass of the above substances. Mix with water and sand mill to prepare a sand mill slurry with a solid content of 30%. The median particle size of the solid substances in the sand mill slurry is 0.3μm~0.4μm by volume reference.
[0077] The obtained sand-milled slurry was spray-dried to obtain the first precursor.
[0078] S2. The first precursor is transferred to a nitrogen atmosphere furnace for a first heat treatment. The temperature of the first heat treatment is 300℃, the time is 2h, and the heating rate is 2℃ / min. The resulting first sintered material is then crushed.
[0079] S3. The second carbonaceous component is mixed with the pulverized first sintered material in a solid-state process to obtain the second precursor. The second carbonaceous component includes carbon nanotubes and reduced graphene oxide, with carbon nanotubes accounting for 0.3% of the mass of the second precursor and reduced graphene oxide accounting for 0.1% of the mass of the second precursor.
[0080] S4. The second precursor is transferred to a nitrogen atmosphere furnace for a second heat treatment. The temperature of the second heat treatment is 550℃, the time is 10h, and the heating rate is 2℃ / min, finally obtaining the cathode material.
[0081] Comparative Example 3
[0082] S1. Take FePO4·2H2O, NaH2PO4, and Na2CO3 in a molar ratio of 2.6:1:1.3, and add 7.2% glucose and 2% citric acid by mass of the above substances. Mix with water and sand mill to prepare a sand mill slurry with a solid content of 30%. The median particle size of the solid substances in the sand mill slurry is 0.1μm~0.2μm by volume reference.
[0083] The obtained sand-milled slurry was spray-dried to obtain the first precursor.
[0084] S2. The first precursor is transferred to a nitrogen atmosphere furnace for a first heat treatment. The temperature of the first heat treatment is 300℃, the time is 2h, and the heating rate is 2℃ / min. The resulting first sintered material is then crushed.
[0085] S3. The pulverized first sintered material is placed in a nitrogen atmosphere furnace for a second heat treatment. The temperature of the second heat treatment is 550℃, the time is 10h, and the heating rate is 2℃ / min, finally obtaining the positive electrode material.
[0086] Comparative Example 4
[0087] S1. Take FePO4·2H2O, NaH2PO4, and Na2CO3 in a molar ratio of 2.6:1:1.3, and add 4% glucose and 2% citric acid, which account for 4% of the total mass of the above substances. Mix with water and sand mill to prepare a sand mill slurry with a solid content of 30%. The median particle size of the solid substances in the sand mill slurry is 0.1μm~0.2μm.
[0088] The obtained sand-milled slurry was spray-dried to obtain the first precursor.
[0089] S2. The first precursor is transferred to a nitrogen atmosphere furnace for a first heat treatment. The temperature of the first heat treatment is 300℃, the time is 2h, and the heating rate is 2℃ / min. The resulting first sintered material is then crushed.
[0090] S3. The second carbonaceous component is mixed with the pulverized first sintered material in a solid-state process to obtain the second precursor. The second carbonaceous component includes carbon nanotubes and reduced graphene oxide, with carbon nanotubes accounting for 0.6% of the mass of the second precursor and reduced graphene oxide accounting for 0.2% of the mass of the second precursor.
[0091] S4. The second precursor is transferred to a nitrogen atmosphere furnace for a second heat treatment. The temperature of the second heat treatment is 550℃, the time is 10h, and the heating rate is 2℃ / min, finally obtaining the cathode material.
[0092] Characterization and Testing
[0093] 1. The cathode material prepared in Example 1 was subjected to XRD testing. The testing conditions were: Cu-Kα target, emission wavelength λ = 0.154 nm, scanning voltage 40 kV, current 100 mA, scanning mode was step scanning, and the scanning range was 5°~80°. The obtained XRD spectrum is shown below. Figure 1 As shown. (From the appendix) Figure 1 It can be seen that the positions and shapes of the diffraction peaks of this material are in good agreement with the standard crystal structure characteristics of sodium iron pyrophosphate. No characteristic diffraction peaks of obvious impurity phases were observed in the spectrum, indicating that the prepared cathode material has high phase purity and a relatively complete crystal structure.
[0094] 2. The cathode materials prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to carbon content testing, compaction density testing, electronic conductivity testing, and electrochemical performance testing, respectively. The test data are summarized in Table 1, and some electrochemical curves are shown in the appendix. Figure 2 .
[0095] (1) Carbon content testing equipment: HW2000C arc infrared carbon-sulfur analyzer.
[0096] (2) Compacted density test method: accurately weigh 1g of each positive electrode material powder, place it in a hard mold with a diameter of 13mm, press it under 3t pressure and then calculate the density.
[0097] (3) Electronic conductivity testing method: The electronic conductivity of each cathode material at room temperature was determined using the powder four-probe method. Before testing, each cathode material powder was dried in a vacuum oven at 105℃ for 4 hours to fully remove the moisture adsorbed on the surface and inside of the material. Then, equal amounts of each dried cathode material powder were accurately weighed and placed in a hard mold with a diameter of 13 mm. The mold was pressed under a pressure of 10 MPa for 60 s to form a circular sheet with a thickness of 2.2~3.6 mm. Three independent samples of each type were prepared in parallel. The resistivity of the obtained sheets was measured using a four-probe resistance meter. During the test, the four-probe probe was perpendicularly contacted with the center area of the sample. Each sample was rotated at least three different positions to collect data in order to eliminate the measurement deviation caused by the difference in test points. The resistivity of each sample was calculated based on its thickness and cross-sectional area, and then the corresponding electronic conductivity was obtained. Finally, the arithmetic mean of the three parallel samples was taken as the electronic conductivity test result of the group of samples.
[0098] (4) Electrochemical performance testing methods:
[0099] Electrochemical performance testing was conducted using CR2032 coin cells. First, the various positive electrode materials were mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 90:5:5, with an appropriate amount of N-methylpyrrolidone added as a dispersant. After grinding and mixing until homogeneous, a homogeneous slurry was obtained. The resulting slurry was uniformly coated onto one side of an aluminum foil and dried under vacuum at 120℃ for 10 hours. After drying, the electrode was rolled using a roller mill and then cut into circular electrode sheets with a diameter of 1.3 cm using a slicing machine. The active material loading was controlled at 10 mg / cm³. 2 The battery assembly was completed in an argon atmosphere glove box, where the water and oxygen pressures were controlled below 0.1 ppm. A sodium metal sheet was used as the counter electrode. The electrolyte consisted of 1 M NaClO4 as the solute and a 1:1 volume ratio of ethylene carbonate and diethyl carbonate as the solvent, with 5% fluoroethylene carbonate added to the total volume of the aforementioned mixed solvent.
[0100] The assembled test battery was subjected to constant current charge-discharge testing at room temperature. The charging process involved constant current charging to 4.0V (vs. Na / Na) at a current density of 24 mA / g. + ), and then discharged at the same current density to 2.0V (vs. Na / Na). + Record the first-cycle charge specific capacity and first-cycle discharge specific capacity of each cathode material, and calculate the first coulombic efficiency accordingly.
[0101] Table 1
[0102]
[0103] Analysis of the data in Table 1 shows that, under the premise that the total content of carbonaceous components is approximately 2.0%, Comparative Example 3, which only uses the first carbonaceous component for coating, achieves the highest compaction density of 2.23 g / cm³. 3 However, its electronic conductivity is only 1.31 × 10⁻⁶. -4 The S / cm efficiency in the first week was only 87.84%, indicating that the effect of the first carbonaceous layer formed solely by the pyrolysis of organic carbon sources on improving the conductivity of the material is limited. In contrast, the electronic conductivity of all embodiments and comparative examples that simultaneously introduced the first and second carbonaceous components for gradient carbon coating was significantly improved, demonstrating that the introduction of carbon nanotubes and reduced graphene oxide in the second carbonaceous component plays a positive role in constructing a highly efficient conductive network.
[0104] Comparing Examples 1, 2, and 2, the main difference lies in the median particle size of the solids in the milled slurry. Data shows that as the particle size of the solids in the milled slurry decreases, the particles of the first precursor gradually become finer, and the distribution of the organic carbon source becomes more uniform, which is beneficial for the formation of the subsequent conductive network. Therefore, the electronic conductivity of the resulting cathode material gradually increases. Meanwhile, the median particle size of the resulting cathode material is approximately 8 μm to 10 μm. The milling particle size is only used to control the primary particle size of the precursor and does not change the secondary particle size of the final powder. Therefore, the compaction density of each sample does not fluctuate significantly with changes in milling particle size and remains at 2.10 g / cm³. 3 ~2.11g / cm 3 about.
[0105] Comparing Example 1 and Comparative Example 1, the difference lies in the type of inorganic carbon nanomaterials in the second carbonaceous component: Comparative Example 1 only added carbon nanotubes as the second carbonaceous component, while Example 1 added both carbon nanotubes and reduced graphene oxide. With the same amount of carbon nanotubes, the introduction of a small amount of sheet-like reduced graphene oxide for compounding resulted in an increase in the electronic conductivity of the cathode material from 1.55 × 10⁻⁶ in Comparative Example 1. -4 S / cm increased to 3.61 × 10⁻⁶ in Example 1. -4 The discharge specific capacity increased from 100.538 mAh / g in Comparative Example 1 to 102.749 mAh / g in Example 1 in the first week, indicating that the sheet structure of reduced graphene oxide and the linear structure of carbon nanotubes synergistically combine to construct a more complete multidimensional conductive network, significantly improving the conductivity and capacity of the material. However, the introduction of sheet-like reduced graphene oxide creates a small number of pores between particles, resulting in a slight decrease in compaction density.
[0106] Comparing Examples 1, 3, and 4, the difference lies in the mass ratio of the first carbonaceous component to the second carbonaceous component, i.e., the relative amount of the second carbonaceous component added. Data shows that as the relative proportion of the second carbonaceous component increases, the electronic conductivity of the material continuously increases, from 3.88 × 10⁻⁶ in Example 3. -4 The S / cm ratio was increased to 5.53 × 10⁻⁶ in Comparative Example 4. -4 The S / cm ratio indicates that more one-dimensional carbon nanotubes and two-dimensional reduced graphene oxide contribute to the construction of a richer conductive framework. However, the excessive addition of the second carbonaceous component also has negative effects: on the one hand, the excessive inorganic carbon nanomaterials introduce a large number of pores during particle stacking, resulting in a decrease in compaction density from 2.11 g / cm in Example 1. 3 It decreased to 1.91 g / cm³, as in Comparative Example 4. 3 On the other hand, the reduction in the amount of organic carbon source added reduces the proportion of the first carbonaceous component generated in situ, which is not conducive to the formation of a continuous and dense conductive coating layer on the surface of the primary particles. This affects the charge transport efficiency between the primary particles, resulting in a significant decrease in the charge and discharge specific capacity of the material. The charge specific capacity and discharge specific capacity of Comparative Example 4 decreased to 110.634 mAh / g and 98.514 mAh / g in the first week, respectively.
[0107] Therefore, there is an optimal range for the mass ratio of the first carbonaceous component to the second carbonaceous component. While an excessively low mass ratio is beneficial for improving conductivity, it will sacrifice compaction density and specific capacity, making it difficult to achieve a balanced optimization of comprehensive electrochemical performance.
[0108] The above are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A gradient carbon-coated modified sodium iron pyrophosphate cathode material, characterized in that, The cathode material comprises secondary particles formed by the agglomeration of primary particles. The primary particles include an active material matrix and a first carbonaceous layer covering the outside of the matrix. The secondary particles include agglomerates of primary particles and a second carbonaceous layer covering the outside of the matrix. The first carbonaceous layer and the second carbonaceous layer contain a first carbonaceous component, and the second carbonaceous layer also contains a second carbonaceous component. The first carbonaceous component is an organic carbon source pyrolysis product, and the second carbonaceous component includes at least one of one-dimensional inorganic carbon nanomaterials and two-dimensional inorganic carbon nanomaterials.
2. The gradient carbon-coated modified sodium iron pyrophosphate cathode material according to claim 1, characterized in that, The total mass of the first carbonaceous component and the second carbonaceous component accounts for 1.5% to 2.5% of the total mass of the cathode material, the mass ratio of the first carbonaceous component to the second carbonaceous component is (2 to 4):1, and the mass ratio of the one-dimensional inorganic carbon nanomaterial to the two-dimensional inorganic carbon nanomaterial is (3 to 5):
1.
3. The gradient carbon-coated modified sodium iron pyrophosphate cathode material according to claim 1, characterized in that, The organic carbon source pyrolytes include any one or more of sucrose pyrolytes, glucose pyrolytes, citric acid pyrolytes, starch pyrolytes, and polyethylene glycol pyrolytes; the one-dimensional inorganic carbon nanomaterials include carbon nanotubes; and the two-dimensional inorganic carbon nanomaterials include reduced graphene oxide.
4. The gradient carbon-coated modified sodium iron pyrophosphate cathode material according to claim 1, characterized in that, The chemical formula of the active material matrix is Na. 4-x Fe 3-y (PO4) 2-z P2O7, where: 0<x≤0.6, 0<y≤0.6, 0<z≤0.6, (4-x):(3-y)=(1.32~1.42):
1.
5. The method for preparing the gradient carbon-coated modified sodium iron pyrophosphate cathode material according to any one of claims 1-4, characterized in that, Including the following steps: Iron source, sodium source, phosphorus source, organic carbon source and water are mixed and sand-milled, and the resulting sand-milled slurry is spray-dried to obtain the first precursor; The first precursor is subjected to a first heat treatment, and the resulting first sintered material is pulverized. The second carbonaceous component is mixed with the pulverized first sintered material in a solid phase to obtain the second precursor. The second precursor is subjected to a second heat treatment to obtain the cathode material.
6. The method for preparing gradient carbon-coated modified sodium iron pyrophosphate cathode material according to claim 5, wherein the organic carbon source accounts for 6% to 9% of the total mass of the iron source, the sodium source and the phosphorus source; the solid content of the sand milling slurry is 20% to 40%, and the volume-based median particle size of the solid matter in the sand milling slurry is 0.1 μm to 0.3 μm; the spray drying conditions are: inlet air temperature 180 to 260°C, outlet air temperature 90 to 130°C.
7. The method for preparing gradient carbon-coated modified sodium iron pyrophosphate cathode material according to claim 5, wherein the first heat treatment is carried out in an inert atmosphere, the temperature of the first heat treatment is 200~400℃, the time is 2h~6h, and the heating rate is 1℃ / min~5℃ / min; the pulverization treatment is air jet milling, and the volume-based median particle size of the pulverized first sintered material is 2μm~5μm.
8. The method for preparing gradient carbon-coated modified sodium iron pyrophosphate cathode material according to claim 5, wherein the second carbonaceous component accounts for 0.3% to 1% of the total mass of the second precursor; the second heat treatment is carried out in an inert atmosphere, the temperature of the second heat treatment is 500 to 600°C, the time is 6 to 12 hours, and the heating rate is 1°C / min to 5°C / min.
9. The method for preparing gradient carbon-coated modified sodium iron pyrophosphate cathode material according to claim 5, wherein the iron source comprises any one or more of elemental iron, ferrous oxalate, ferric phosphate, ferric phosphate dihydrate, ferric oxide, ferrous oxalate, ferric nitrate, ferric pyrophosphate, and ferrous pyrophosphate; the sodium source comprises any one or more of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, sodium pyrophosphate, sodium oxalate, and sodium acetate; and the phosphorus source comprises any one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, ferric pyrophosphate, sodium pyrophosphate, and sodium dihydrogen phosphate.
10. The application of the gradient carbon-coated modified sodium iron pyrophosphate cathode material according to any one of claims 1-4 in an electrochemical energy storage device.
